ANALISIS SEBARAN AREA KOMODITAS UNGGULAN PERTANIAN TANAMAN PANGAN DI KABUPATEN BREBES - Darmawan, Ariyanto; Hayati, Rahma; Hariyanto, Hariyanto (Geo-Image, 2017)
The aims of this research are:1) Knowing commodity comparatively superior and competitive, 2) Knowing the rate of growth in the popularity of food crops, 3) Knowing what are the priority commodities and 4) Knowing the spatial distribution superior commodities. The sampling technique purposive sampling. The primary data obtained directly from the farmer to the instrument in the form of a questionnaire. Secondary data were obtained from the agency the Central Bureau of Statistics and the Department of Agriculture and Horticulture. The results showed that: paddy rice field comparatively superior based on analysis Location Quetient (LQ) with the most extensive distribution area, covering 10 districts. Commodities superior competitive basis based on the analysis of Revenue Cost (R/C) with the highest grade in the class of food crops are green beans. The growth rate of the region based on the analysis of the Shift Share (component proportional shift and differential share) is positive in District Tonjong. Commodities are prioritized to be developed is a commodity that includes a first priority, the paddy rice, dry rice, maize, cassava, sweet potato and peanut spread over 10 districts.